2022
DOI: 10.3934/amc.2020109
|View full text |Cite
|
Sign up to set email alerts
|

Further results on 2-uniform states arising from irredundant orthogonal arrays

Abstract: The notion of an irredundant orthogonal array (IrOA) was introduced by Goyeneche andŻyczkowski who showed an IrOA λ (t, k, v) corresponds to a t-uniform state of k subsystems with local dimension v (Physical Review A. 90 (2014), 022316). In this paper, we construct some kinds of 2-uniform states by establishing the existence of IrOA λ (2, 5, v) for any integer v ≥ 4, v = 6; IrOA λ (2, 6, v) for any integer v ≥ 2; IrOA λ (2, q, q) and IrOA λ (2, q + 1, q) for any prime power q > 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Goyeneche and Życzkowski [14] had established a link between the irredundant orthogonal arrays and t-uniform states since 2014, IrOA and t-uniform states has been paid great attention by many scholars, and then there are some results for uniform states [10,44,45] and irredundant orthogonal arrays [26,30,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Goyeneche and Życzkowski [14] had established a link between the irredundant orthogonal arrays and t-uniform states since 2014, IrOA and t-uniform states has been paid great attention by many scholars, and then there are some results for uniform states [10,44,45] and irredundant orthogonal arrays [26,30,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…For t = 3, s = 4, 5, although there exists a 3-uniform state of 7 qudits with local dimension s, it is clear that the existence of an IrOA(N, 7, s, 3) ⇐⇒ the existence of an IrOA(s 4 , 7, s, 3) ⇐⇒ the existence of an OA(s 4 , 7, s, 4), which is a very difficult problem. Recently, Zang et al [42] studied the existence of the IrOA with factor k = 5, 6 and almost solved the existence of these arrays from Lemma 1.1 and Lemma 1.2. Chen et al [4] showed that there exists an IrOA(v 3 , 12, v, 2) for any v ≥ 4 and v ≡ 2 (mod 4) and there exists an IrOA(v 3 , 3v, v, 2) for any prime or prime power v. Li et al [26] gave the existence of irredundant orthogonal arrays with parameters IrOA(q n , k, q, 2), where q is a prime power and q n−1 −1 q−1 + 3 ≤ k ≤ q n −1 q−1 + 3 for n ≥ 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations